2018
DOI: 10.1155/2018/7410801
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Helicobacter pylori Infection and Metabolic Abnormality in General Population: A Cross-Sectional Study

Abstract: Background Previous studies have suggested a link between Helicobacter pylori (H. pylori) and metabolic abnormality. This study aimed at investigating the correlation between H. pylori infection and metabolic abnormality in a general population. Methods All enrolled participants underwent a carbon-13 urea breath test (13C-UBT). For each individual, the following data were collected: age, gender, alanine transaminase (ALT), total protein, albumin, cholesterol, triglyceride (TG), high-density lipoprotein cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 40 publications
2
42
0
2
Order By: Relevance
“…Of these potential eligible articles, we excluded 13 articles (characteristics of excluded articles see Table ) by examining the abstracts or full‐texts carefully for more detailed assessment. Finally, fifteen studies met the inclusion criteria and were included in our meta‐analysis. The detailed flowchart of selection process of eligible studies is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these potential eligible articles, we excluded 13 articles (characteristics of excluded articles see Table ) by examining the abstracts or full‐texts carefully for more detailed assessment. Finally, fifteen studies met the inclusion criteria and were included in our meta‐analysis. The detailed flowchart of selection process of eligible studies is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…As to H. pylori testing method, seven studies used UBT, four used serology to detect antibodies to H. pylori , one used RUT, one used SAT, and two used multiple methods . Regarding confounders adjustment, only five studies did not adjust for confounders . The confounders were obviously different across remaining ten studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, most studies reported higher rates of H pylori ‐I in NAFLD patients and, inversely, higher rates of NAFLD in H pylori ‐infected individuals (Table ). However, a minority of studies reported no association between H pylori ‐I and NAFLD . Only one study reported inverse association, that is, lower rates of NASH in H pylori ‐infected than noninfected individuals; in the same study, H pylori ‐infected individuals had higher rates of steatosis than noninfected ones, which is a seeming paradox .…”
Section: Clinical Studies On the Association Between Helicobacter Pylmentioning
confidence: 96%
“…Following the aforementioned initial reports, there have been amounting data from observational studies (mostly cross‐sectional) having evaluated the potential association between H pylori ‐I and NAFLD . The main characteristics and results of these studies are summarized in Table .…”
Section: Clinical Studies On the Association Between Helicobacter Pylmentioning
confidence: 99%